2017
DOI: 10.1038/onc.2017.204
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between progesterone receptors and retinoic acid receptors in regulation of cytokeratin 5-positive breast cancer cells

Abstract: Half of estrogen receptor-positive breast cancers contain a subpopulation of cytokeratin 5 (CK5)-expressing cells that are therapy resistant and exhibit increased cancer stem cell (CSC) properties. We and others have demonstrated that progesterone (P4) increases CK5+ breast cancer cells. We previously discovered that retinoids block P4 induction of CK5+ cells. Here we investigated the mechanisms by which progesterone receptors (PR) and retinoic acid receptors (RAR) regulate CK5 expression and breast CSC activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 60 publications
2
37
0
Order By: Relevance
“…RARα is a common and necessary co-factor at many ER transcribed genes in breast cancer cells (43). Furthermore, we have observed co-recruitment of PR and RARα at sequences resembling PREs and RAREs in breast cancer cells (44). Our results also imply that PR has a general impact on Pol III transcription and could possibly affect ribosome function since 5S rRNA abundance was depressed by P4 and MPA (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…RARα is a common and necessary co-factor at many ER transcribed genes in breast cancer cells (43). Furthermore, we have observed co-recruitment of PR and RARα at sequences resembling PREs and RAREs in breast cancer cells (44). Our results also imply that PR has a general impact on Pol III transcription and could possibly affect ribosome function since 5S rRNA abundance was depressed by P4 and MPA (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Analyzing clinical data in a comprehensible manner, we found an association between higher tumor grade at diagnosis and overexpression of KRT5 in CTCs at V1, which is the gene that encodes CK5. CK5-positive BC cells have enhanced mammosphere forming potential and are endocrine and chemotherapy-resistant in MBC [38]. However, KTR5 expression has not been reported yet on CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel blocks the G2/M phase of cell cycle and induces cancer cell apoptosis. 33 As shown in Figure 5B Figure 5D). Real-time PCR showed that compared with that in cells transfected with control plasmids, the expression of CD44 mRNA was down-regulated in paclitaxel-resistant cells transfected with ERa-shRNA ( Figure 5E).…”
Section: Knockdown Of Era Significantly Decreased Cd44 Gene Expressmentioning
confidence: 66%
“…Indeed, compared with that in control cells, the expression of ERα and CD44 protein was down‐regulated in paclitaxel‐resistant cells treated with IBC (Figure A). Paclitaxel blocks the G2/M phase of cell cycle and induces cancer cell apoptosis . As shown in Figure B and C, IBC could increase the proportion of cells in G2/M phase as determined by flow cytometry in MCF‐7/R cells treated with paclitaxel.…”
Section: Resultsmentioning
confidence: 83%